2019
DOI: 10.5213/inj.1938076.038
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Multicenter, Open-Label Study of Dose Escalation Therapy in Male Patients With Nocturia Refractory to 0.2-mg Tamsulosin Monotherapy

Abstract: To investigate the efficacy and safety of 0.4 mg of tamsulosin in patients with nocturia not responding to 0.2 mg. Methods: Patients with intractable nocturia after treatment with 0.2 mg of tamsulosin for > 1 month were included in a multicenter, prospective, observational, single-arm study. Patients were prescribed 0.4 mg of tamsulosin and followed up for 2 months to assess nocturnal voiding and nocturia-related bother. Changes in the mean number of nocturnal voids, the proportion of 50% responders, 3-day fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Our results are in accordance with those that treatment with 0.4 mg of tamsulosin in patients with nocturia not responding to 0.2 mg reduced nocturia from 2.71 to 1.98 per night. 10 It has been reported that alpha adrenergic blockers ameliorate the function of bladder storage by increasing bladder blood flow and/or inhibiting urethral afferent activity. 18 , 19 Therefore, it could be reasonably speculated that tamsulosin 0.4 mg increased nocturnal bladder capacity and sequentially reduced nocturia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in accordance with those that treatment with 0.4 mg of tamsulosin in patients with nocturia not responding to 0.2 mg reduced nocturia from 2.71 to 1.98 per night. 10 It has been reported that alpha adrenergic blockers ameliorate the function of bladder storage by increasing bladder blood flow and/or inhibiting urethral afferent activity. 18 , 19 Therefore, it could be reasonably speculated that tamsulosin 0.4 mg increased nocturnal bladder capacity and sequentially reduced nocturia.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Recent studies have reported that increasing the dose of tamsulosin to 0.4 mg is effective and safe in Asian men with LUTS who do not respond to an initial dose of 0.2 mg tamsulosin. 9 , 10 , 11 , 12 However, it is still unclear whether tamsulosin 0.4 mg as the initial dose is effective and safe in Asian men with LUTS. To the best of our knowledge, only one randomized clinical, double-blind, phase 3 trial has been reported thus far.…”
Section: Introductionmentioning
confidence: 99%
“…The voiding diary is a useful method to show the patient’s real-life voiding habits and patterns. Therefore, in many lower urinary tract diseases such as overactive bladder and benign prostate hyperplasia, voiding diary is included in the research method as an essential evaluation ( Choi et al, 2018 ; Chuang et al, 2018 ; Hsiao et al, 2019 ; Lee et al, 2018 ; Yu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%